Respuesta :

Answer:

x = 6, y = -5.

Step-by-step explanation:

6x + 8y = -4

-6x - 10y = 14    Adding will eliminate  the terms in x:

0 - 2y = 10

y = 10/-2 = -5,

Plug this into the second equation:

-6x - 10(-5) = 14

-6x = 14 - 50 = -36

x = -36/-6

x = 6.

Answer:

x = 6

y = -5

Step-by-step explanation:

Add the 2 together because the 6x and -6x cancel out

   6x + 8y = -4

+(-6x - 10y = 14)

        -2y = 10

        [tex]\frac{-2y}{-2} = \frac{10}{-2}[/tex]

       y = -5

Then plug into y to get x.

 6x + 8(-5) = -4

  6x - 40 = -4

      + 40 + 40

  6x = 36

  [tex]\frac{6x}{6}  = \frac{36}{6}[/tex]

 x = 6

ACCESS MORE